2004
DOI: 10.1158/1078-0432.ccr-04-0322
|View full text |Cite
|
Sign up to set email alerts
|

Heteroclitic CD33 Peptide With Enhanced Anti-Acute Myeloid Leukemic Immunogenicity

Abstract: The goal of these studies was to engineer a synthetic CD33 peptide with enhanced immunogenicity for the induction of acute myeloid leukemia (AML)-specific CTLs. Eight modified CD33 peptides YLISGDSPV, YIGSGDSPV, YII-IGDSPV, YIILGDSPV, YIISGISPV, YIISGDLPV, YIIS-GDSWV and YIISGDSPL were designed for increased HLA-A2.1 or T cell receptor affinity and compared with the native CD33 65-73 peptide, AIISGDSPV, for enhanced immunogenicity. The YLISGDSPV peptide was found to be the most immunogenic epitope producing hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Recent studies showed that ligation of CD33 molecules mediated AML cell growth inhibition, [7][8][9][10] activation of protein tyrosine phosphatases SHP-1 and SHP-2, 3-5 and a recruitment of the Syk protein tyrosine kinase. 28,29 These events led to apoptosis and inhibition of cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that ligation of CD33 molecules mediated AML cell growth inhibition, [7][8][9][10] activation of protein tyrosine phosphatases SHP-1 and SHP-2, 3-5 and a recruitment of the Syk protein tyrosine kinase. 28,29 These events led to apoptosis and inhibition of cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…As GO is widely used in the treatment of AML, 10 but effective only in one-third of patients, understanding the mechanisms of its cytotoxicity is important. We hypothesize that determining Syk expression before treatment can serve as a biomarker and, therefore, increase the efficacy of GO or unconjugated anti-CD33 mAb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bae et al predicted a number of modified CD33 peptides with potentially enhanced immunogenicity [63,64]. Their modifications, in the form of single amino acid replacement, were designed to increase HLA-A*0201 or TCR affinity when compared to the native CD33…”
Section: Cd33mentioning
confidence: 99%
“…In this respect, modification of native peptides in solid tumours, leukaemia, or lymphomas led to peptides with increased immunogenicity against tumour cells [41][42][43][44][45]. On the basis of these findings, one would think that our immune system has failed to eliminate tumours not because tumour antigens were absent, but rather because appropriate lymphocytes were not activated to a threshold required for tumour rejection.…”
Section: Overcoming Immune Tolerance To Tumour Antigensmentioning
confidence: 99%